The Influence of the Recruitment and Promotion Process on the Performance of Human Resources Staff Employees at the Headquarters of the Republic of Indonesia Police - Ilham Taufiiqulhakim; Yuni Pratikno; Jamal Hanaffy (Dinasti Publisher, 2026)
This study aims to analyze the influence of recruitment and promotion processes on employee performance, both partially and simultaneously, in the Career Development Bureau Staff of the Indonesian National Police Headquarters. The focus of this study is based on the important role of human resource management, particularly in the appropriate recruitment process and objective, transparent, and performance-based job promotions, as strategic factors in improving employee performance. Effective recruitment is expected to produce competent employees who are in accordance with organizational needs, while job promotions serve as a means of career development and employee work motivation. This study uses a quantitative approach with a survey method, where data is collected through a structured questionnaire compiled based on the indicators of each research variable. To complement the quantitative analysis, this study is also supported by qualitative data in the form of respondents' statements in the questionnaire, consultation results, and brief interviews with relevant informants to obtain a more comprehensive picture of empirical conditions in the field. The study population was 133 Career Development Bureau Staff employees, with a research sample of 100 respondents determined using appropriate sampling techniques. Data analysis was conducted using SPSS version 27 software to test the partial and simultaneous effects between variables. The results of the study indicate that the recruitment process (X1) and job promotion (X2) partially have a positive and significant effect on employee performance (Y). In addition, simultaneously the two independent variables also have a significant effect on employee performance. The coefficient of determination (R-Square) value of 0.407 indicates that 40.7% of employee performance variation can be explained by the recruitment and job promotion process, while the remaining 59.3% is influenced by other factors outside this research model. This finding emphasizes the importance of optimizing the recruitment and job promotion process as a strategic effort to improve employee performance within the National Police Headquarters